Simulation and optimization of a tuneable rectangular microstrip patch antenna based on hybrid metal-graphene and FSS superstrate for fifth-generation applications - Nidal Qasem; Hamzah M. Marhoon (Universitas Ahmad Dahlan, 2020)
In this paper, a tuneable rectangular microstrip patch antenna (MPA) is simulated and optimized to operate in four frequency bands of the next generation of wireless communication systems. The proposed design incorporates a copper radiating patch with four implanted graphene strips for tuning purposes. The reconfigurable surface impedance of graphene can easily be altered by applying a DC voltage bias directly to the graphene strips, allowing the operating frequency of the antenna to be tuned as desired. The capability of the applied voltage to tune the operating frequency band of the proposed antenna is studied via computer simulation technology (CST) microwave studio (MWS). Frequency selective surfaces (FSSs) are introduced in order to improve the radiation parameters of the antenna. The operating frequency band of the tuneable rectangular MPA increases directly as the applied DC voltage bias is increased. Based on the simulation results, a tuneable rectangular MPA placed between two FSSs is proposed for fifth-generation applications.